Community Support of Sexual Minority Adolescents - Christine Regan; Kate Fogarty (EDIS)
FCS-9234, a 3-page fact sheet by Christine Regan and Kate Fogarty, is one in a series of discussions on understanding teen sexuality. It aims to provide staff and volunteers working in community-based settings with positive information and practical tips on how to create a welcoming, safe environment for LGBT adolescents. Includes resources and reference. Published by the UF Department of Family Youth and Community Sciences, August 2006.